Affective state of ethnic community as related to gender and marital status (Dhaka University Journal of Biological Sciences, 2013)
The study was aimed at understanding the affective state of Bangladeshi ethnic community in relation to gender and marital status. Towards this end, positive and negative affects of 103 adult indigenous persons were measured. Analysis of data in multiple regressions demonstrated that both gender and marital status are significantly associated with positive affect (Gender: β = 0.318, p < 0.001; Marital status: β = 0.201, p < 0.05) but not with negative affect. Results indicated that the indigenous males have 0.32 standard deviations increased positive affect as compared to the indigenous females and that married individuals have 0.20 standard deviations increased positive affect as compared to their unmarried counterparts. Along with previous studies the present study advances the understanding that gender and marital status inequalities in affect are not specific to a particular community; rather it is a generalized picture of all societies. In general, men possess more positive affect than females; married persons possess more positive affect than the unmarried persons.Dhaka Univ. J. Biol. Sci. 22(2): 155-161, 2013 (July)